Roles of mindfulness and depressive symptoms on the association between adverse childhood experiences and non-suicidal self-injury - Guangzhe F. Yuan; Yanping Lu; Yuan Tao; Wei Shi (European Journal of Psychotraumatology)
Background: Prior research has indicated that adverse childhood experiences (e.g. emotional abuse and emotional neglect) may be a contributing factor in the development of non-suicidal self-injury (NSSI) in emerging adulthood. Yet, the data on the potential psychological mechanism underlying adverse childhood experiences and NSSI are limited.Objective: The objective of this study was to examine the serial mediating roles of mindfulness and depressive symptoms on the relation between emotional abuse and neglect and NSSI.Method: A cross-sectional design was used in the current study. A sample of 10,839 Chinese youth (Mage = 19.75, SD = 1.26, age range: 15–30 years; 74.9% women) completed online self-report measures assessing childhood emotional trauma, mindfulness, depressive symptoms, and NSSI behaviours.Results: Structural equation modelling results showed that emotional abuse was negatively related to mindfulness and positively related to depressive symptoms and NSSI. Emotional neglect was negatively related to mindfulness and positively related to depressive symptoms. Mindfulness and depressive symptoms serially mediated the association between emotional abuse and emotional neglect and NSSI.Conclusions: These findings highlight the complex interplay among childhood emotional trauma, mindfulness, depressive symptoms, and NSSI in adolescents and young adults. While this cross-sectional study identifies potential associations, causal relations cannot be established. Future longitudinal research is needed to determine whether interventions aimed at enhancing mindfulness and reducing depressive symptoms may be effective in reducing the risk of NSSI among individuals with a history of emotional abuse or neglect.